2020
DOI: 10.9734/cjast/2020/v39i4831214
|View full text |Cite
|
Sign up to set email alerts
|

AMMI Biplot Analysis for Genotype X Environment Interaction and Stability for Yield in Hybrid Rice (Oryza sativa L.) Under Different Production Seasons

Abstract: The aim of the study was to determine the genotype x environment interaction and stability performance of fifteen rice hybrids in three different production seasons during 2016, 2017 at Regional Agricultural Research Station, Warangal, Telangana.  Data was subjected to the additive mean effects and multiplicative interaction (AMMI) analysis, results indicated that significant genotype x environmental interaction (GEI) influenced the relative ranking of the hybrids across the seasons. It was evident from AMMI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…In the present study, the rice landraces, G10 (Chandikar) and G5 (Kuruvaikalanjium) were found to be more sensitive to environments. Similar results were previously reported by Devi et al (2020). The striking feature of what-won-where GGE biplot is its ability to show the what-won-where pattern of a genotype by environment.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the rice landraces, G10 (Chandikar) and G5 (Kuruvaikalanjium) were found to be more sensitive to environments. Similar results were previously reported by Devi et al (2020). The striking feature of what-won-where GGE biplot is its ability to show the what-won-where pattern of a genotype by environment.…”
Section: Resultssupporting
confidence: 89%
“…This implied that the first two principal components are enough to explain the interaction effects of 15 rice landraces in five production years/seasons. These findings are in agreement with the findings of Devi et al (2020). Biplots are graphs where both genotypes and environments are plotted on the same axes that interrelationships can be visualized (Anowara et al 2014).…”
Section: Resultssupporting
confidence: 81%
“…However, G6 (WGL 1370) and G8 (MTU 1010) were plotted near to zero IPCA1 axis indicating that these hybrids are relatively more stable across locations. The genotype, G4 (WGL 1367), was found superior among all the genotypes as well as over the checks and across all the environments under study.These findings were in agreement with Rukmini Devi et al [26], Kesh et al [23], Mohan et al [17], Siddi et al [27].The remaining genotypes had less than the mean grain yield and found specific adaptation to few tested environments. Likewise, Jain et al [28] reported that "genotypes with PC1 scores close to zero are usually widely adapted and they were considered more stable in their performance across test environments".…”
Section: Ammi 1 Biplotsupporting
confidence: 90%
“…Comparably, Mary et al, (2019) reported that the biplot for yield during the wet season showed that G10 was the winner genotype in E4, and G7 in E8 and E9. Rukmini Devi et al, (2020) reported the rice genotypes, G2 (WGRH-6) and G3 (WGRH-10), had better performance in mega environment E3 and the genotype, G9 (WGRH-18), exhibited better…”
Section: What-won-where Bi-plotmentioning
confidence: 99%